Limited distribution of cratonic strike-slip faults in Sichuan basin and their genesis mechanisms - Liu, Zijing; Su, Nan; Liu, Shaobo; Chen, Zhuxin; Tang, Pengcheng; Wu, Saijun; Wang, Lining; Ren, Rong; Hao, Cuiguo; Miao, Zhengshuo (Frontiers in Earth Science, 2025)
IntroductionThe genesis mechanism of cratonic strike-slip faults in the Sichuan basin is not yet fully resolved, largely due to the lack of comprehensive characterization of fault distribution, which constrains the understanding of the relationship between fault development and tectonic events.MethodIn this study, we supplement extensive three-dimensional seismic data from areas beyond central Sichuan to delineate fault distribution across the entire basin. By integrating these findings with regional tectonic processes, the genesis mechanisms of these faults are proposed.ResultThe results reveal that cratonic strike-slip faults are exclusively concentrated in central Sichuan and the Weiyuan area, with no such faults observed elsewhere in the basin. This spatial restriction suggests that their formation was governed by the unique tectonic evolution of central Sichuan.DiscussionFurthermore, three lines of evidence prove that multi-stage uplifts played a pivotal role in fault development: (1) Faults of varying orientations exhibit distinct development periods, aligning with regional uplift phases; (2) Fault orientations correlate with the bending directions of strata induced by uplifts; and (3) Additional examples of analogous faults in Jurassic strata near the foreland front uplift further corroborate the link between fault orientation and strata bending caused by uplift processes. The central Sichuan region, characterized by superimposed multi-phase paleo-uplift evolution, thus serves as the focal zone for these faults. It is also inferred that the so-called “cratonic strike-slip” fault system in central Sichuan is not a genuine strike-slip system but rather a composite of normal faults with different directions and periods. The genesis of these normal faults is attributed to the tensile strain resulting from strata bending during uplift events. This study not only provides a more comprehensive characterization of fault distribution but also introduces a novel genetic model for these faults, which provides crucial data and new ideas for improving the theory of the fault system within the basins.